2017
DOI: 10.1038/srep41852
|View full text |Cite
|
Sign up to set email alerts
|

EpEX/EpCAM and Oct4 or Klf4 alone are sufficient to generate induced pluripotent stem cells through STAT3 and HIF2α

Abstract: Epithelial cell adhesion molecule (EpCAM) was reported to be cleaved into extracellular domain of EpCAM (EpEX) and intracellular domain of EpCAM (EpICD). We previously reported that EpCAM serves as a potent stem cell marker which is highly and selectively expressed by undifferentiated rather than differentiated hESC. However, the functional role of EpCAM remains elusive. Here, we found that EpEX and EpCAM enhance the efficiency of OSKM reprogramming. Interestingly, Oct4 or Klf4 alone, but not Sox2, can success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…Furthermore, we provide evidence that the soluble ectodomain EpEX, which is produced upon RIP of EpCAM [ 39 , 48 , 110 ] including HNSCC cell lines ( Fig 3 ), is a regulatory ligand of EGFR that induces ERK1/2 and AKT signaling ( Fig 9 ). The definition of EpEX as a ligand for EGFR is in line with recent reports on the activation of EGFR signaling after treatment with EpEX in mouse embryonic fibroblasts and in colon carcinoma cell lines [ 71 , 111 ]. In colon carcinoma cells, EpEX induced mild proliferation and regulated proteolysis of intact EpCAM molecules through the activation of ADAM17 and γ-secretase [ 111 ].…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, we provide evidence that the soluble ectodomain EpEX, which is produced upon RIP of EpCAM [ 39 , 48 , 110 ] including HNSCC cell lines ( Fig 3 ), is a regulatory ligand of EGFR that induces ERK1/2 and AKT signaling ( Fig 9 ). The definition of EpEX as a ligand for EGFR is in line with recent reports on the activation of EGFR signaling after treatment with EpEX in mouse embryonic fibroblasts and in colon carcinoma cell lines [ 71 , 111 ]. In colon carcinoma cells, EpEX induced mild proliferation and regulated proteolysis of intact EpCAM molecules through the activation of ADAM17 and γ-secretase [ 111 ].…”
Section: Discussionmentioning
confidence: 58%
“…Since Yamanaka's factors (Sox2, Oct3/4, Klf4, and c‐Myc) were discovered for cell reprogramming, many studies have been conducted to establish more effective methods for inserting the glis family zinc finger 1 (Maekawa et al, ). The STAT3 signal regulates the expression of HIF‐2α, and this STAT3‐HIF‐2α pathway has been examined for its involvement in reprogramming and stemness processes in human iPS cells (Kuan et al, ). In this study, the relationship between STAT3 and the regulation of the pluripotency in human iPS cells was investigated using two specific inhibitors that suppressed the dimer formation and nuclear translocation of STAT3 (Schust, Sperl, Hollis, Mayer, & Berg, ; Siddiquee et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown either how these factors, used in the present study, enhance stat3 expression or which one of them plays a crucial role in the activation. However, recent study has shown that Oct4 or Klf4 alone, but not Sox2, can successfully reprogram fibroblasts into induced pluripotent stem cells with the help of epithelial cell adhesion molecule (a trans-membrane protein) and its extracellular domain (a soluble protein), via activation of Stat3, which leads to the nuclear-translocation of HIF2α 30 . This study provides an evidence to show that Oct4 and Klf4 of the four factors may play a crucial role in activation of Stat3 and again supports our above argument.…”
Section: Discussionmentioning
confidence: 99%